PENGGUNAAN MEDIA PAPAN PINTAR TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK SD - Wahyuni, Ratna; Nasution, Haryati Ahda (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2024)
AbstractLearning media is very important to bridge abstract Mathematics concepts into a more concrete form. This study aims to examine the impact of using smart board media on mathematics learning outcomes in elementary school, especially on multiplication and division materials. This study uses quantitative data as the type of data. Quantitative data collection was conducted using a test that adopted a pretest and posttest with a control group design to obtain the data. The results showed the impact of using smart board media on math learning achievement. The results showed that the learning outcomes of the experimental class increased more significantly than the control class, with a difference of 7.41. This difference indicates the influence of the learning media applied to students, affecting their learning outcomes. Furthermore, the calculated t value of 2.617 was obtained in the hypothesis test, which is greater than the t table, which is 2.005, so the hypothesis test is accepted. This result confirms that the smart board media effectively improves learners' numeracy skills, especially in multiplication and division. Abstrak Media pembelajaran memiliki peran penting dalam menjembatani konsep matematika yang abstrak menjadi lebih konkret. Penelitian ini bertujuan untuk mengkaji pengaruh penggunaan media papan pintar terhadap hasil belajar matematika siswa sekolah dasar, khususnya pada materi perkalian dan pembagian. Penelitian ini menggunakan desain quasi eksperimen dengan metode posttest only design. Sampel Penelitian ini terdiri dari 30 orang peserta didik pada kelas eksperimen dan 26 orang peserta didik pada kelas kontrol. Data dikumpulkan melalui instrument tes yang telah divalidasi. Data yang diperoleh dianalisis menggunakan uji t. Hasil penelitian menunjukkan pencapaian hasil belajar siswa di kelas eksperimen dan kelas kontrol dengan selisih rata-rata sebesar 7,41. Uji hipotesis menghasilkan nilai t sebesar 2,617 dengan signifikansi 0,05. Dapat disimpulkan bahwa media papan pintar efektif digunakan dalam meningkatkan kemampuan numerasi siswa. Temuan ini menegaskan pentingnya penggunaan alat pembelajaran inovatif dalam meningkatkan keterlibatan dan pemahaman siswa terhadap matematika.